Pengajaran Bahasa Arab di Madrasah Ibtidaiyah Kota Metro - Akla Akla (Jurusan PGMI FTIK IAIN Metro Lampung, 2020)
This study was based on three questions (1) how are the problems felt by students in the process of learning Arabic? (2) what is the current level of motivation for learning Arabic in Madrasah Ibtidaiyahstudents today? (3) what is the current level of Arabic mastery of Madrasah Ibtidaiyah students? Toanswer this, class observations, questionnaires and language skills were evaluated. This study showsthat learning Arabic in Madrasah Ibtidaiyah Negeri 3 Metro City experiences various difficulties.Difficulties felt by students are not being able to master Arabic. Students cannot identify the meaningof the mufradat that is heard, cannot speak about daily activities, cannot read fluently and fluently andexperience various difficulties in writing Arabic. These difficulties are triggered by learning processesthat are less oriented towards active students. Students are not involved in learning optimally. And thelanguage environment that is not conducive and does not support the language learning process. Thisweak Arabic learning process causes low student motivation which, in turn, impacts on the achievementof students’ mastery in Arabic language. This study suggests the need for action studies to overcomedifficulties in the learning process.